Additions to knowledge of the paper wasp Polistes delhiensis Das and Gupta, 1989 (Hymenoptera: Vespidae: Polistinae) from Vietnam with description of the male and nest - Nguyen, Lien Thi Phuong; Nguyen, Cuong Quang; Bozdoğan, Hakan (Zootaxa, 2018)
Notes on the paper wasp of the genus Polistes, Polistes delhiensis Das and Gupta, 1989 (Hymenoptera: Vespidae: Polistinae) from Vietnam are presented. The species has two color forms of the clypeus: brightly colored specimens were collected in the southern part of the range and darker colored specimens were collected in the northern part. Based on morphological and DNA data analysis, it is confirmed that both color forms belong to Polistes delhiensis. The male of this species is described for the first time and its fully-developed nest is also described.